Sustained delivery of finasteride by biodegradable system - Chen, Hui Wen (2017)
Androgenic alopecia is a common hair loss disease found in men which occurs due to hair miniaturization when hair follicles weaken and cause gradual loss of hairs. In the past, the common medication used was minodixil which provided a therapeutic effect of up to 50% of the males. However, in recent years, finasteride was found to have a higher improvement of hair counts compared to minodixil and hence it was widely used as an alternative treatment for hair loss found in men. The current treatment of finasteride was through the oral route which requires daily intake of the drug. Hence in this study, another method which is the in situ polymer precipitation will be investigated to reduce the dosages and improve patient compliance. The in situ polymer precipitation uses polymeric implant technique where finasteride will be encapsulated into the polymer gel which is made up of PLGA 50:50 0.4A, triacetin and N-Methyl-2-pyrrolidone. The polymer gel samples will then be injected into phosphate buffer solution to mimic the human body condition. The amount of drug release will be analysed using high performance liquid chromatography and release profile will be plotted to evaluate the drug release behavior. This study was conducted to investigate the effects of different polymer gel composition and different shapes of the polymer gel injected. It was found that with higher amount of triacetin and lower amount of ￼formulation, there will be a more constant finasteride release profile with low initial burst release. This is attributed to its slow inverting system where solvent affinity with N-Methyl-2-pyrrolidone present in the ￼￼water is low, thus reducing solvent diffusion with limited burst release. In addition, it was also shown that in fast inverting system, the initial burst release was dependent of surface area of the depot. This is due to extensive polymer lean phases and large pores in the morphology which increase both the water influx rate and diffusion of the drug. On the other hand, the initial burst in slow inverting system is independent of surface area due to extensive polymer rich phases and smaller pores in the morphology. This led to lower water influx and inhibits the diffusion of drug. While in subsequent release, both the fast inverting and slow inverting systems is independent of surface area due to polymer walls entrapping the drug and lower water influx.